Transformation of the sovereignty of national economies in the world in the context of regional studies (Economics and region, 2025)
The article presents the author's statement of the problem of understanding the trends of the regional economy and the corresponding content of regionalism, both in the conditions of a regular process of globalization, and in the conditions of not always predictable circumstances, the provocation of trade wars in the world in the spring of 2025, which triggered trends. The tendency of development of regional relations in the context of centralization trends in the world and trends in the sovereignty of national economies is analyzed. The relevance of the analysis of the process of transformation of the sovereignty of national economies is explained by the need to understand the further development of its forms in the ratio of trends of centralization and decentralization, in the form of regionalization in the world. Recent events in the world space, including the tariff policy of the United States Administration, headed by President D. Trump, requires an adequate approach to understanding the content and transformation of economic policy, including regional economic policy in modern globalization. The question arises in the need to understand the essence, that is, cause and effect relationships of the regional economy in modern conditions, and above all, relatively modern vision of retrospective and trends of its development in the conditions of globalization changes. It is noteworthy as a terminological concept of the concept of regional economy in the context of globalization changes, as well as the rotation of the evolution of the regional economy and its useful forms, and itself: Economic unions, currency unions, trade blocks, regional globalization, city financial centers, etc. The fact that over time, the problems of regional science change over time, transformation of problems of regional science-is a process of changing scientific approaches, tasks and methods used to study spatial development, regional policy, socio-economic differentiation of territories and management of regional development. Thus, the main task is to publish and substantiate the author's concept of the problem of development of regionallogy in the context of globalization, trends of centralization and sovereignty of both national economies, and its new forms of manifestation in modern autocratic economic manifestations in the world.
Keywords: regionalism; trend; decentralization; centralization; globalization; sovereignty